When anger hurts : quieting the storm within - McKay, Matthew; Rogers, Peter D. (Peter Denny), 1941-; McKay, Judith; Johnson, Kirk. (Oakland, CA : New Harbinger Publications, 1989)
A self-help book providing exercises and techniques for achieving anger control and stress reduction.
How to use this book -- The myths of anger -- The physiological costs of anger -- The interpersonal costs of anger -- Anger as a choice: the two-step model of anger -- Who's responsible? -- Combating trigger thoughts -- Controlling stress step by step -- Stopping escalation -- Coping through healthy self-talk -- Response choice rehearsal -- Problem-solving communication -- Images of anger -- Anger as a defense -- Anger and children -- Spouse abuse.
Includes bibliographical references (p. [313]-320)
Also issued online.
Keywords: Anger